Paradigms in clinical psychology: Intrapsychic and interpersonal perspective of evidence-based psychological intervention models - Camacho-Mata, Dacia Yurima (Universidad Autónoma de Tamaulipas, 2015)
Psychotherapy is largely influenced by the theoretical concepts of psychology such as individualistic court which considers the personality as an attribute of the court which considers the social and environmental effect on the personality. The objective of this work to review the convergence and divergence of the theoretical and practical aspects of the cognitive behavioral model (intrapsychic paradigm) and the interpersonal and systemic models. These paradigms, far from being opposed, can share their contributions and have benefits in the practical exercise. For this reason, looking at the roots of each model to find coincidences at the epistemological level, allows the coherent and logical integration of both: theories and techniques, conforming a new therapeutic paradigm that enhances the psychotherapy benefits for patients. Archive XML (SciELO)